Pengeboran Minyak Bumi Secara Ilegal di Aceh Perspektif Fiqih Siyasah (Studi Kasus Tambang Minyak Ilegal di Aceh) - Maulana, Faiz Ahwal; Lubis, Syofiaty (UNES Law Review, 2023)
Illegal oil drilling in Aceh from the perspective of siyasah fiqh is a violation of state law and order. Fiqa siyasah or political fiqh is a part of the science of fiqh which discusses the relationship between the government and the people, as well as procedures for governing the state. In Siyasah fiqh, the government must protect public interests and uphold justice in society. The research method used in this writing is a normative juridical type of research (legal research), namely research that focuses on examining the application of rules or norms in positive law. Drilling illegal oil wells is a criminal act, carried out by the community to produce oil using traditional drilling tools such as used pipes and used tanks, without permission from the government and without considering the risks to the surrounding environment. That law enforcement for oil drilling perpetrators does not have to wait for the activity to be classified as an extra ordinary crime.